Philosophy of Science as a Foundation for Critical Thinking in Everyday Life - Sarah Zakia Rahman; Ma'rifah Nurul Hikmah; Tamsik Udin (Bibliotheca: Journal of Philosophy, 2026)
This research aims to analyze the role of the philosophy of science as a fundamental foundation in shaping critical thinking patterns relevant to the problems of everyday life. Using a qualitative research method with a literature review approach (library research), the author examines literature related to epistemology, ontology, and axiology to dissect the mechanisms of human reasoning. The results of the study conclude that the philosophy of science is not merely a theoretical academic discipline, but a practical instrument that enables individuals to validate information, avoid logical fallacies, and make decisions based on systematic logic. By understanding the pillars of science, individuals are able to maintain a constructively skeptical stance toward social phenomena and the massive flow of digital information. The significant contribution of this research lies in the integration of philosophical values into concrete actions, which ultimately enhances the quality of literacy and the intellectual sharpness of society in facing the complexities of contemporary social reality.